Superioritas Yesus Kristus dan Aplikasinya dalam Gereja Masa Kini dalam Surat Ibrani - Ester Br Ginting; Joy Sopater Wasiyono (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2022)
The divinity of Jesus Christ is often questioned and debated by certain circles, both past and present. The letter to the Hebrews describes Jesus Christ as the light of God's glory and the image of God's own being. Jesus Christ is the Son of God, who will possess all things that are revealed to be God, and atone for the sins of mankind, is the main channel of revelation, which is higher than the prophets and angels. The description of Jesus as the Great High Priest in the letter to the Hebrews (Hebrews 4:14-16). Priesthood Superiority of Jesus Christ built on the Melchizedek typology. the writer of Hebrews finds congruence between Christ and Melchizedek. Typological results prove that the priesthood of Jesus Christ is superior to the priesthood of Levi, where Christ is a greater priest than the priest of Levi and he himself has been replaced; and only His priesthood can draw sinners closer to God and communicate with God. and the only perfect and final priesthood can offer the atoning sacrifice, once and for all. In Hebrews there are several warnings that also relate to followers of Christ today. We are warned not to waste the salvation that has been handed down to us. Jesus Christ is already seated at the right hand of the Father, and because He will defeat His enemies and establish His kingdom, and we inherit that victory of salvation. We must hold fast to our faith to the end.